Does Racial and Ethnic Discrimination Vary Across Minority Groups? Evidence from Three Experiments - Leigh, A; Varganova, E; Booth, A (My University, 2009)
We conducted several large-scale field experiments to measure labor market discrimination across different minority groups in Australia – a country where one quarter of the population was born overseas. To denote ethnicity, we used distinctively Anglo-Saxon, Indigenous, Italian, Chinese, and Middle Eastern names, and our goal was a comparison across multiple ethnic groups rather than focusing on a single minority as in most other studies. Our main experiment, an audit discrimination study, involved sending over 4000 fictional resumes to employers in response to job advertisements. In all cases, we applied for entry-level jobs and submitted a CV showing that the candidate had attended high school in Australia. We found economically and statistically significant differences in callback rates, suggesting that ethnic minority candidates would need to apply for more jobs in order to receive the same number of interviews. These differences vary systematically across groups, with Italians (a more established migrant group) suffering less discrimination than Chinese and Middle Easterners (who have typically arrived more recently). We also conducted two additional experiments to form a more nuanced picture of prejudice. These were a ‘Return to Sender’ experiment and an Implicit Association Test. The results from both experiments reveal societal prejudice against minority groups, although the ranking sometimes differs from that in the audit discrimination study.
Keywords: Culture; Disadvantage -- Discrimination; Employment; Culture -- Culturally and Linguistically Diverse; Disadvantage; Labour market; Disadvantage; Employment; Culture; Culturally and Linguistically Diverse; Discrimination; Employment and unemployment